Tengku Mahkota Pahang ordered to focus specifically on the importance and empowerment of TVET - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 1 June 2024 - His Majesty the Tengku Mahkota of Pahang Tengku Hassanal Ibrahim Alam Shah Ibni Al-Sultan Abdullah Ri'ayatuddin Al-Mustafa Billah Shah Pro-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) ordered to focus specifically on the importance and empowerment of TVET.